Feasibility and Effectiveness of Indicator Condition-Guided Testing for HIV: Results from HIDES I (HIV Indicator Diseases across Europe Study) - Sullivan, Ann K.; Raben, Dorthe; Reekie, Joanne; Rayment, Michael; Mocroft, Amanda; Esser, Stefan; Leon, Agathe; Begovac, Josip; Brinkman, Kees; Zangerle, Robert; Grzeszczuk, Anna; Vassilenko, Anna; et al. (PloS one, 2013)
Improved methods for targeting HIV testing among patients most likely to be infected are required; HIDES I aimed to define the methodology of a European wide study of HIV prevalence in individuals presenting with one of eight indicator conditions/diseases (ID); sexually transmitted infection, lymphoma, cervical or anal cancer/dysplasia, herpes zoster, hepatitis B/C, mononucleosis-like illness, unexplained leukocytopenia/thrombocytopenia and seborrheic dermatitis/exanthema, and to identify those with an HIV prevalence of >0.1%, a level determined to be cost effective. A staff questionnaire was performed. From October 2009- February 2011, individuals, not known to be HIV positive, presenting with one of the ID were offered an HIV test; additional information was collected on previous HIV testing behaviour and recent medical history. A total of 3588 individuals from 16 centres were included. Sixty-six tested positive for HIV, giving an HIV prevalence of 1.8% [95% CI: 1.42-2.34]; all eight ID exceeded 0.1% prevalence. Of those testing HIV positive, 83% were male, 58% identified as MSM and 9% were injecting drug users. Twenty percent reported previously having potentially HIV-related symptoms and 52% had previously tested HIV negative (median time since last test: 1.58 years); which together with the median CD4 count at diagnosis (400 cell/uL) adds weight to this strategy being effective in diagnosing HIV at an earlier stage. A positive test was more likely for non-white individuals, MSM, injecting drug users and those testing in non-Northern regions. HIDES I describes an effective strategy to detect undiagnosed HIV infection. All eight ID fulfilled the >0.1% criterion for cost effectiveness. All individuals presenting to any health care setting with one of these ID should be strongly recommended an HIV test. A strategy is being developed in collaboration with ECDC and WHO Europe to guide the implementation of this novel public health initiative across Europe.